Production & characterization of multi-walled carbon nanotube (mwcnt) reinforced polyester - Joshua Singh, Mantar Singh (2014)
This paper presents the study on the production and characterization of Hydroxyl functional Multi-Walled Carbon Nanotube (MWCNT) reinforced Polyester composite. The main objective of this study is to optimize the weight percentage of MWCNT in the composite and the sonication time of the composite. To determine the optimum weight percentage of MWCNT, samples with different weight percentage of MWCNT was prepared. The prepared samples were sonicated for one hour and were tested for its viscosity. From the result, the viscosity was the highest at 0.6wt % MWCNT. Hence, the optimum weight percentage of MWCNT is at 0.6wt %. After optimizing the weight percentage of MWCNT, the sonication time was optimized. This was done by preparing samples of 0.6wt % MWCNT which was then sonicated at different time intervals. After sonication, the viscosity was determined. From the result, it can be concluded that the optimum sonication time of 0.6wt % MWCNT is 1.5 hour. After optimization, the composite was then characterized and tested using Tensile Strength (TS) test, Thermal Gravimetric Analysis (TGA) and Fourier Transform Infrared Spectroscopy (FTIR). From the Tensile Strength test, it can be concluded that the composite with 0.6wt % MWCNT was stronger than the sample with pure Polyester. On the other hand, TGA results show that the optimized composite has higher thermal stability than pure Polyester. As a conclusion, this Polyester composite has the potential to be used in various applications due to its high mechanical strength and high thermal stability.